PENGARUH KOMPLEKSITAS TUGAS, TEKANAN ANGGARAN WAKTU, DAN INDEPENDENSI AUDITOR TERHADAP PERILAKU DISFUNGSIONAL AUDITOR DAN IMPLIKASINYA PADA KUALITAS AUDIT - Rohman, Akhmad (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This study aims to examine the factors that influence dysfunctional auditor behavior and its implications on audit quality. This research develops theoretical framework as the basis of hypothesis, to answer the research questions consisting of: (1) how the effect of task complexity to dysfunctional auditor behavior, (2) how the effect of time budget pressure to dysfunctional auditor behavior, (3) how the effect of auditor independence on dysfunctional auditor behavior, and (4) how the effect of dysfunctional auditor behavior on audit quality. The sample of this research is 80 people auditor Inspectorate of Banten Province. This research uses census method. Data are primary data collected through questionnaires. The method of data analysis to test the hypothesis is regression analysis using Statistical Package for Social Sciences 22 (SPSS 22). The results of this study indicate that: (1) task complexity has a positive effect on the dysfunctional auditor behavior, (2) time budget pressure has a positive effect on the dysfunctional auditor behavior, (3) independence of the auditor negatively affects the dysfunctional auditor behavior, and (4) dysfunctional auditor behavior has a negative effect to audit quality.Â Keywords: task complexity, time budget pressure, auditor independence, dysfunctional auditor behavior, and audit quality